Comparison of misoprostol doses in termination of pregnancy in the first trimester - Hosainatoo, Reem Mostafa; Ramadan, Lina Salman; Youssef, Ahmad Hasan (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to compare the efficacy of vaginal misoprostol with different doses for abortion in the first trimester. Patients and Methods: Descriptive Comparative Study conducted for the period one year (July 2020 –July 2021) at Tishreen University Hospital in Lattakia- Syria. The study included 80 pregnant women in the first trimester who had a therapeutic indication for termination of pregnancy after taken consent from it and her fathers, and were divided into group A was (40 women): were administrated 400 µg of vaginal misoprostol and repeated every 6 h for 48 h, and group B was (40 women): were administrated 800 µg of vaginal misoprostol repeated after 24 h. Results: Abortion rate after the first dose in group B was higher than group A (67.5% vs.10%). The rate of complete abortion was significantly higher in group B (72.5%) vs. (17.5%) in group A, p= 0.0001, and mean induction- abortion interval in group B was significantly shorter than group A (13.8±3.3 vs. 29.4±5.9, p: 0.004). There weren’t significant associations between both indications and results of abortion with the number of pregnancies in the two groups (p>0.05). Nausea was the most frequent side effect in the two groups without significant difference (p>0.05). Conclusion: Misoprostol represents a safe and effective alternative to invasive methods for termination early intrauterine pregnancy.